View Single Post
Old 2020-03-27, 13:09   #6
wpolly
 
wpolly's Avatar
 
Sep 2002
Vienna, Austria

3·73 Posts
Default

Quote:
Originally Posted by retina View Post
Very good.

If we assign:

A = 1 + 1 + 1 + 1 + 1 + 1 + ...
B = 1 + 2 + 3 + 4 + 5 + 6 + ...

Then B - A = B, since pairwise subtraction gives 0 + 1 + 2 + 3 + ... = 1 + 2 + 3 + ...

Therefore A = 1 + 1 + 1 + 1 + 1 + 1 + ... = 0

Sadly, in the regime of regularized sums, we no longer have 0 + 1 + 2 + 3 + ... = 1 + 2 + 3 + ...
wpolly is offline   Reply With Quote